2021
DOI: 10.29359/bjhpa.13.3.09
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of balance and leg muscle strength between tai chi and yoga in older adults: A cross-sectional study

Abstract: Background: There is increasing evidence that practicing tai chi or yoga can improve the elderly’s physical performance. This study aimed to compare the effects of tai chi and yoga on balance and leg muscle strength in the elderly. Material & Methods: This cross-sectional study involved 90 elderly persons who practice tai chi (n = 36), yoga (n = 23), and a control group (n = 31). The balance function was assessed using the single-leg stance (SLS) test, while leg muscle strength (LMS) was assessed using a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Hakim et al detailed that both the Tai Chi and yoga exercise groups illustrated superior balance performance compared to the no-exercise group, 37 while Jelita et al indicated that the yoga group had slightly improved balance (single-leg stance (SLS)) over the Tai Chi group. 19 This happens because yoga is usually done barefoot on less steady surfaces, such as a mat or sand, while tai chi is usually performed on more stable, flat, harder surfaces, such as floor tile or ground. Practicing yoga on a less stable surface may increase the body's vagal action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hakim et al detailed that both the Tai Chi and yoga exercise groups illustrated superior balance performance compared to the no-exercise group, 37 while Jelita et al indicated that the yoga group had slightly improved balance (single-leg stance (SLS)) over the Tai Chi group. 19 This happens because yoga is usually done barefoot on less steady surfaces, such as a mat or sand, while tai chi is usually performed on more stable, flat, harder surfaces, such as floor tile or ground. Practicing yoga on a less stable surface may increase the body's vagal action.…”
Section: Discussionmentioning
confidence: 99%
“…6 studies have examined the effect of yoga, 17,18,21,29,30,34 4 studies have studied Tai chi 22,23,26,32 and 2 studies have evaluated the effect of Tai chi and yoga. 19,37 Pilates has also been used as an intervention in 4 studies, 20,25,31,35 aerobics in 4 studies, 24,27,28,33 and the effect of dance has been studied in 2 other studies. 15,36 All of these 22 studies reported an improvement in balance and fall prevention after dancebased interventions in old people.…”
Section: Details Of Types and Duration Of Interventions Of The Review...mentioning
confidence: 99%
See 1 more Smart Citation